1999
DOI: 10.1897/1551-5028(1999)018<2751:bofaaa>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

BIOAVAILABILITY OF FRESHLY ADDED AND AGED NAPHTHALENE IN SOILS UNDER GASTRIC pH CONDITIONS

Abstract: Abstract-The bioavailability of hydrophobic organic chemicals decreases with aging in soil because of sequestration. However, assessments of the risk of exposure to contaminated soils are usually dependent on either chemical concentrations, which are measured using vigorous extraction methods, or models that assume an equilibrium without considering the actual conditions. The objective of this research was to determine the availability and desorption kinetics of freshly added and aged naphthalene from a peat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…For the assessment of environmental risks associated with PAH-contaminated soil, it is important to evaluate the oral bioavailability of PAHs of ingested soils for humans, especially children. It has been reported that soil contaminants are less 100% available (Pignatello and Xing, 1996;Tang et al, 1998;Jin et al, 1999). Recently, much attention has been directed to the development of in vitro extraction test to mimic human digestion process for estimating bioavailability (Reeves et al, 2001;Jin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For the assessment of environmental risks associated with PAH-contaminated soil, it is important to evaluate the oral bioavailability of PAHs of ingested soils for humans, especially children. It has been reported that soil contaminants are less 100% available (Pignatello and Xing, 1996;Tang et al, 1998;Jin et al, 1999). Recently, much attention has been directed to the development of in vitro extraction test to mimic human digestion process for estimating bioavailability (Reeves et al, 2001;Jin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For the assessment of environmental risks associated with PAHcontaminated soil, it is important to evaluate the oral bioaccessibility of PAHs of ingested soils for humans, especially for children. It has been reported that soil contaminants are less than 100% available (Tang et al 1998;Jin et al 1999). Moreover, given the discrepancies between the physiology of humans and other organisms, as well as the cost and time constraints associated with such studies, a more efficient alternative is desirable (Ruby et al 1999).…”
mentioning
confidence: 99%
“…Two avenues of investigation would be useful in quantifying pesticide bioavailability: the development of standardized biological tools to measure or quantify bioavailability-perhaps at different trophic levels-and the development of nonsolvent-associated chemical methodologies that mimic bioavailability in key soil biota. Other interesting approaches include procedures to mimic the release of residues during passage through the gastrointestinal tract (42,43). In addition, it would be instructive to further exploit advanced analytical methodologies (44), which aim to characterize the form and fate of recalcitrant residues, to confirm their stability and negligible bioavailability or long-term biological significance.…”
Section: Which Is the Way Forward?mentioning
confidence: 99%